Nano-indentation characterization of Ni–Cu–Sn IMC layer subject to isothermal aging - Xu, Luhua; Pang, John H.L. (Thin solid films, 2006)
Lead-free Sn–Ag–Cu(SAC) solder joint on Cu–OSP and ENIG subject to thermal testing leads to IMC growth and causes corresponding reliability concerns at the interface. Modulus and hardness of these IMCs were characterized by Nanoindentation CSM from plan view in this study. A plan-view IMC surface was prepared by deep etching and slight polishing method. When SAC/Ni(Au) solder joint were subject to thermal aging, elastic modulus of the NiCuSn IMC at SAC/ENIG specimen changed from 207 to 146 GPa with different aging time up to 500 h. The hardness decreased from 10.0 to 7.3 GPa. For SAC/Cu–OSP reaction couple, elastic modulus of Cu 6Sn 5 kept constant at 97.0 GPa and hardness about 5.7 GPa. The modulus of Cu 3Sn after 500 h thermal aging was 115.7 GPa. The change of modulus is caused by solid state diffusion process during thermal aging where the morphology and crystal structure of Ni,–Cu–Sn IMC is changing. The calculation of modulus and hardness for IMC layers was based on nanoindentation CSM test results and was compared with reported results.